1983
DOI: 10.1042/bj2140983
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell division by interferons. The relationship between changes in utilization of thymidine for DNA synthesis and control of proliferation in Daudi cells

Abstract: Inhibition of the proliferation of Daudi cells by exposure to human lymphoblastoid interferons is associated with an early and marked decrease in the incorporation into DNA of exogenous [3H]thymidine when cells are incubated with trace amounts of this precursor. In contrast, incorporation of exogenous deoxyadenosine into DNA is unchanged under the same conditions. Interferon treatment results in a lowering of thymidine kinase activity, an effect which may be largely responsible for the inhibition of incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…]leucine (New England Nuclear) was measured by trichloroacetic acid precipitation of protein as described previously [11,12,16,18]. The concentrations and specific radioactivities of these precursors are given in the legends.…”
Section: Cell Culturementioning
confidence: 99%
“…]leucine (New England Nuclear) was measured by trichloroacetic acid precipitation of protein as described previously [11,12,16,18]. The concentrations and specific radioactivities of these precursors are given in the legends.…”
Section: Cell Culturementioning
confidence: 99%
“…We have examined the effects of anti-IgM on various B lymphocyte cell lines, particularly B lymphoblastoid cell lines (8 -10). These results show that anti-IgM induces apoptosis in EBV 1 -negative cell lines (including Ramos and ST486), but induces growth arrest without apoptosis in EBV-positive cell lines (including Daudi and Raji) (this report) (11)(12)(13). This in turn led us to examine in greater detail the molecular events which may precede anti-IgM-mediated induction of apoptosis in Ramos.…”
mentioning
confidence: 99%
“…Initially, the direct cytostatic effect of IFN-a was thought to be the major mechanism by which it inhibits tumor growth (33,34,48); however, subsequent studies revealed that inhibition of angiogenesis and induction of tumor cell apoptosis are other IFN-a mediated antitumor effects (7,10,(49)(50)(51)(52). Our in vitro studies revealed that B16F10 melanoma cells are more sensitive to the cytostatic effects of IFN-a, whereas the CT26 colon carcinoma cells are more sensitive to the proapoptotic properties of rmIFN-a in vitro.…”
Section: Discussionmentioning
confidence: 99%